2021
DOI: 10.1021/acsanm.1c02371
|View full text |Cite
|
Sign up to set email alerts
|

Ag2BiI5 Perovskite Quantum Dots Passivated with Oleylamine Sulfide for Solar Cells and Detection of Cu(II) Ions

Abstract: Improving charge transport properties between the quantum dots (QDs) and reducing the non-radiative recombination have been attempted on silver bismuth iodide (Ag 2 BiI 5 ) perovskite QDs using oleylamine−sulfide passivation. Herein, we have prepared Ag 2 BiI 5 silver bismuth iodide QDs via a simple ligand-assisted reprecipitation method, and the samples were passivated with the oleylamine−sulfide complex. The absorption and emission profiles were red-shifted, which implies that the overall size of the QDs has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 56 publications
(77 reference statements)
0
7
0
Order By: Relevance
“…In addition, PSCs are suffering from significant non-radiative recombination losses originated from defect states of perovskites. Until now, numerous passivating strategies including solvent, composition, and interfacial engineering have been developed to enhance both efficiency and long-term stability. Specially, the buried interface between the perovskite layer and the underlying transport layer has been vastly investigated to minimize trap states and recombination losses as well as facilitate carrier extraction. For example, Dong et al and Gao et al have employed chlorobenzenesulfonic potassium salts and porous organic cages to passivate the buried tin oxide (SnO 2 )/perovskite interface, which results in better energy alignment, reduced trap states, and improved stability. , Similarly, Xu et al reported the successful use of daminozide as an interlayer to modify interface energetics and passivate defects at the interface as well as in perovskite bulk . Although high performance of PSCs has been achieved through the trap-state passivation, the mechanism is still complicated and excellent trap-state passivators are insufficient, which require further exploration and study.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PSCs are suffering from significant non-radiative recombination losses originated from defect states of perovskites. Until now, numerous passivating strategies including solvent, composition, and interfacial engineering have been developed to enhance both efficiency and long-term stability. Specially, the buried interface between the perovskite layer and the underlying transport layer has been vastly investigated to minimize trap states and recombination losses as well as facilitate carrier extraction. For example, Dong et al and Gao et al have employed chlorobenzenesulfonic potassium salts and porous organic cages to passivate the buried tin oxide (SnO 2 )/perovskite interface, which results in better energy alignment, reduced trap states, and improved stability. , Similarly, Xu et al reported the successful use of daminozide as an interlayer to modify interface energetics and passivate defects at the interface as well as in perovskite bulk . Although high performance of PSCs has been achieved through the trap-state passivation, the mechanism is still complicated and excellent trap-state passivators are insufficient, which require further exploration and study.…”
Section: Introductionmentioning
confidence: 99%
“…Design of less hazardous materials to maintain the environmental sustainability is still a challenging task nowadays. , In particular, toxic and biotoxic metal pollution is noted as global threat to the environment, which can be handled using specific detection and quantification tactics. To detect those heavy metal ions, various detection/quantification methods were proposed using organic, inorganic, and hybrid nanomaterials. Among the available hybrid nanomaterials, utilization of luminescent organic–inorganic halide perovskite nanocrystals/quantum dots (PQDs) toward diverse analytes is of great interest to the scientific community. Hybrid PQDs have attracted much attention due to their exceptional applications in solar cells, light-emitting devices, photodetectors, sensors, and so forth. Moreover, detection/quantification of specific metal analytes using the hybrid PQDs-based sensors via a surface tuned sensing process was successfully demonstrated . For example, Lu and co-workers proposed utilization of luminescent CH 3 NH 3 PbBr 3 QDs toward recognition of Hg 2+ with subnanomolar detection limit (LOD) by means of surface-mediated sensing tactics .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the same team presented a modified solvothermal method by changing the ligand to oleylaminesulfide for improved photoelectric properties and obtained nanocrystals with an average size of ≈5 nm. [115] Overall, solid-state synthesis methods enable the formation of phase-pure crystals. However, high energy intensity and cost associated with the use of high vacuum and high-temperature conditions limit their extension toward practical applications.…”
Section: Quantum Dot Synthesismentioning
confidence: 99%
“…Recently, the same team presented a modified solvothermal method by changing the ligand to oleylamine‐sulfide for improved photoelectric properties and obtained nanocrystals with an average size of ≈5 nm. [ 115 ]…”
Section: Synthesis and Thin‐film Depositionmentioning
confidence: 99%